TINDAK PIDANA PENIPUAN DENGAN MENGGUNAKAN SARANA TELEKOMUNIKASI (HANDPHONE) - Dewi, Ni Komang Ratih Kumala (Jurnal Advokasi, 2017)
The emergence of concerns about criminal fraud by means of telecommunication containing an information on receiving the prize for winning a lottery, this crime has been troubling the community because they disturb the comfort in the use of communication devices or mobile phones. The number of people who believe the message conveyed by the perpetrators and refuses to obey commands such as sending told sejumnlah high nomalnya money into the account of the perpetrator. Masyakarkat is expected to be more careful against various forms of crime because we never know when we will become victims of crime so it should be instilled in us to always be careful in acting.